'Public Management Modernisation Programme' : country case study : Guyana - Grogan, Soyinka (CARICAD [St. Michael]TT, 2006)
Presents background information on Guyana, its economy, macroecoomic policies, government, politics, judicial system and domestic and international challenges. Focuses on the Public Management Modernisation Programme.